2023
DOI: 10.1177/10732748231169396
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of Tumour-Infiltrating Lymphocytes (TILs) are Associated with a Better Prognosis, While CDK5 Plays a Different Role Between Nonmetastatic and Metastatic Colonic Carcinoma

Abstract: Objective We investigated the prognostic value of cyclin-dependent kinase 5 (CDK5) in a true population-based cohort of patients with colon cancer. Methods 1. Immunohistochemical (IHC) staining was used to retrospectively analyse the expression of CDK5 in colon cancer tissue samples of 296 patients. The χ2 test, Kaplan-Meier method and Cox proportional regression model were used to analyse the difference between the patients with differential expression of CDK5 and with different stages (metastatic and nonmeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The differential expression patterns of miR-142-5p were observed in cancer tissues [150][151][152][153][154]. A downstream target gene of miR-142-5p is cyclindependent kinase 5 (CDK5) [39], whose role has been found in the development and progression of many cancers [155][156][157] and neurodegenerative [158,159] and inflammatory disorders [160][161][162]. Sui et al [39] demonstrated that miR-142-5p directly inhibits the CDK5mediated upregulation of inflammatory cytokines in acquired middle ear cholesteatoma, making it a potential therapeutic target in this disease.…”
Section: Microrna-142-5pmentioning
confidence: 99%
“…The differential expression patterns of miR-142-5p were observed in cancer tissues [150][151][152][153][154]. A downstream target gene of miR-142-5p is cyclindependent kinase 5 (CDK5) [39], whose role has been found in the development and progression of many cancers [155][156][157] and neurodegenerative [158,159] and inflammatory disorders [160][161][162]. Sui et al [39] demonstrated that miR-142-5p directly inhibits the CDK5mediated upregulation of inflammatory cytokines in acquired middle ear cholesteatoma, making it a potential therapeutic target in this disease.…”
Section: Microrna-142-5pmentioning
confidence: 99%